MODEL HUBUNGAN KEPEMIMPINAN, STRES KERJA, KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PERUSAHAAN JASA PENGIRIMAN KARGO DI KOTA - Siagian, Mauli; Wasiman, Wasiman (REKAMAN (Jurnal Riset Ekonomi Bidang Akuntansi dan Manajemen), 2018)
Cargo shipping service companies are one of the supporting factors for various companies performing their performance, especially goods or manufacturing companies. Whether or not the companys performance can be seen based on employee performance. The higher the enthusiasm of employees in work will further increase the potential of a company to achieve its goals. This study aims to examine the extent to which the role of leadership, work stress, organizational commitment and job satisfaction is able to improve the performance of employees of Cargo Shipping Services in Batam City, using quantitative research methods with data analysis techniques with path analysis of employees. The results of this study are; Leadership has a significant direct effect on job satisfaction. Job stress has a significant direct effect on job satisfaction. Organizational commitment has a significant direct effect on job satisfaction. Job satisfaction has a direct and insignificant effect on employee performance. Leadership has a direct and insignificant effect on employee performance. Job stress has a significant direct effect on employee performance. Organizational commitment has a significant direct effect on employee performance. Leadership has a significant effect through job satisfaction on employee performance. Job stress has a significant effect through job satisfaction on employee performance. Organizational commitment does not significantly influence job satisfaction on employee performance.